Rice pellets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Researchers at the Walloon Agricultural Research Centre of Gembloux, Belgium, are testing a new fuel in Senegal.